(untitled) (The Pakistan Development Review, 2012)
This paper explores the idea of Inclusive Growth as it has evolved over time since the Industrial Revolution in the West, and in the developing countries since 1950, when development economics and development policy were officially born. It is defined as a policy that deliberately seeks to achieve concurrently a dynamic relationship between the growth of per capita income, the distribution of income and the level of poverty in a growing society. The active pursuit of this three-pronged objective must, therefore, be the basic aim of development policy. Experience shows that this relationship, though generally true, is by no means automatic, nor is it amenable to quick fixes. The main premise of the present paper is that without inclusive growth the standard of living of a people cannot be raised on a permanent basis. The paper argues that to succeed in grasping the Holy Grail will require a major rethinking of development policies to guide developing countries along a high-growth trajectory. In particular, development policies that the fast-growers (especially the miracle-growers of East Asia and now China) have pursued must also form part of the policy-packages of developing countries together with measures to promote high rates of saving to finance the investment requirements of a fast-growing economy, and government-supported import-substituting industrialisation, among others. Yet, the policies of the fast-growers need not be imitated blindly. But they should be adjusted to take into account new knowledge about the development process. To institutionalise growth on a long-term basis, governments must also prepare a new social contract to lay firm foundations of a dynamic society based on social justice; which, in turn, requires a creative synergy of economic, political and social forces at work in the society.